Design of Ready-to-Use “Ball-in-Ball” Staphylococcus aureus Microsphere Based on Novel Cryoprotectant and Drop Freeze-Drying Technology: Effective Preservation and Application - Zile Wang; Dongdong Chen; Xiaomei Zheng; Yuqing Li; Shaoqian Jiang; Yanfei Chen; Jingjian Jia; Libo Yu; Tao Peng (Foods)
Staphylococcus aureus (S. aureus) poses a significant threat to public health and safety, and enhancing the monitoring of S. aureus in food is essential to curb and prevent foodborne transmission. In order to obtain strains for more convenient and rapid use in quality control or quantitative analysis, this study designed a ready-to-use “ball-in-ball” microsphere based on a novel cryoprotectant combined with drop freeze-drying technology. When using a cryoprotectant that contains 1.5% bovine serum albumin, 4.5% trehalose, 8.2% polyethylene glycol 8000, and 4.1% D-mannitol, the survival rate of S. aureus can reach 98.2 ± 2.6%. This cryoprotectant effectively prevents S. aureus from shrinking, deforming, and damaging cell walls. Additionally, it shows desirable protective efficiency for other Gram-positive bacteria. The molding of microspheres is efficient and cost-effective, demonstrating good uniformity and stability without the need for pre-freezing. The moisture content and the count of S. aureus showed no significant changes over 90 days at −20 °C. In the simulated contaminated sample, the recovery rate of S. aureus in milk and green tea was 83.1–93.7%. This study could provide a practical approach to improve the monitoring efficiency of S. aureus and shows potential as a generalized strategy for preparing ready-to-use strains related to food safety.